Annual Plan 1999-2000 Statements Union Territory of Pondicherry - Planning Commission (Planning Commission, 1999)
Government of Pondicherry Planning and Research Department, Shipping, Roads & Bridges, Tourism, Survey & Statistics, Civil Supplies, Technical Education, Social Services, Water Supply & Sanitation, Information & Publicity, Welfare and Development of Disabled, Social Defiance Programme, Other Social Services, Forestry & Wild-Life.
Union Territory of Pondicherry
Government of Pondicherry Planning and Research Department
Keywords: Plantations; Agricultural Financial Institutions; Special Progrramme for Rural Development; Land Reforms; Community Developments & Panchayats; Major & Medium Irrigation; Non-Conventional Sources of Energy; Integrated Rural Energy Progrramme; Village & Small Industries; Ports & Light Houses; Civil Aviation; Inland Water Transport; Ecology & Environment; Secretariat Economic Services